PENINGKATAN RETENSI BUAH MANGGA KULTIVAR GADUNG 21 DENGAN PEMBERIAN NAA DAN GA3 INCREASING RETENTION OF MANGO FRUIT CULTIVAR GADUNG 21 BY NAA AND GA APPLICATION 3 - , Sakhidin; Purwoko, Bambang Sapta (Pembangunan Pedesaan, 2005)
The objective of the research was to study the effect of NAA and GA application 3 on fruit retention of mango cv. Gadung 21. The experiment was conducted from July to December 2002, located at mango orchard of PT Fajar Mekar Indah, Pasuruan. A randomized block design with two factors was used in this experiment. The first factor was concentration of NAA, i.e., 0, 10, 30, and 100 ppm. The second one was concentration of GA , i.e. 0, 30, and 100 ppm. Each treatment was 3 replicated three times. Result of the research showed that the application of NAA inclined to reduce percentage of fruit drop per panicle. The application of 100 ppm NAA gave the highest number of fruit per panicle (1.03) and weight of fruit per tree (20.55 kg). The application of 100 ppm GA gave the highest weight of fruit 3 per tree (20.52 kg). Interaction between concentration of NAA and GA did not 3 influence all observed variables.